Physical and Mechanical Properties of Soybean Plants and their Relationships - SESSIZ, Abdullah (Journal of Agricultural Engineering, 2003)
Physical and mechanical properties of soybean plants as well as their correlation with each other were determined for its use in the development of non-conventional harvesting-threshing devices. Plant uprooting force, pod detachment force, plant cross-sectional shear force, shear strength, root length, stem thickness, and plant height were determined for SA-88, A-31/37 and A-39/35 soybean cultivars. Pod numbers and pod detachment force; root length and plant uprooting force, stem thickness and plant uprooting force, stem diameter and shear force, root length and plant length, root length and stem thickness, plant height and stem thickness were significantly correlated for three cultivars. Uprooting force depended on stem diameter and cultivars, and varied between 92-255 N for 6.0-8.5 mm diameters, cross-sectional shear force varied between 549.1-1594.7 N, shear strength of soybean varied between 1941.26-3753.61 N/cmÂ². Also, statistical analysis indicated that there was a significant difference between three soybean cultivars in terms of physical and mechanical properties.